Association of grain yield with identifiable plant characteristics of corn hybrids in the west-central Great Plains - Frank, Brian J.; Schlegel, Alan J.; Stone, Loyd R.; Kirkham, Mary B. (My University, 2013)
Water supply for crop use is the primary factor controlling corn (Zea mays L.) grain yield in the west-central Great Plains. With water supply varying as production systems range from dryland through irrigated, selecting hybrids for optimum yield in the anticipated water environment is vital for success. Our objective was to analyze a group of corn hybrids and determine: a) are there significant differences in identifiable plant characteristics among the hybrids and b) are there significant associations between identifiable plant characteristics and grain yield. Corn was grown near Tribune, KS, in 3 yr in two fields; one dryland and one irrigated. Hybrids (18) replicated in four blocks were grown at each field, with dryland and irrigated results analyzed separately. From linear regression, no significant correlation existed between irrigated grain yield and days to initial silking of hybrids in any of the 3 yr. The correlation between dryland grain yield and days to initial silking of hybrids was significant (P<0.05) in all 3 yr, with grain yield decreasing as days to initial silking increased. Dryland grain yield was also significantly and negatively correlated with dry stover mass in all 3 yr and with tiller population in 2 of 3 yr. Hybrids selected for dryland in the west-central Great Plains should be from the earlier 1/3 or 1/2 of the 98- to 118-d relative maturity (RM) range of our study. In addition, hybrids selected for dryland should have characteristics of smaller stature (less stover) and non-tillering plants.
Grain yield and plant characteristics of corn hybrids in the Great Plains
Citation: Frank, Brian J., Alan J. Schlegel, Loyd R. Stone, and Mary Beth Kirkham. “Grain Yield and Plant Characteristics of Corn Hybrids in the Great Plains.” Agronomy Journal 105, no. 2 (2013): 383–94. https://doi.org/10.2134/agronj2012.0330.
Keywords: Zea mays; Corn; West-central Great Plains; Water supply; Corn hybrids/maize hybrids; Grain yield